Assessing the Implementation Fidelity of a School-Based Teaching Personal and Social Responsibility Program in Physical Education and Other Subject Areas - Escartí, Amparo; Liops-Goig, Ramon; Wright, Paul M (Journal of teaching in physical education, 2018)
Purpose: The Teaching Personal and Social Responsibility (TPSR) model was developed to foster responsibility and teach life skills that transfer to various settings. The purpose of this study was to assess the implementation fidelity of a school-based TPSR program in physical education and other subject areas. Method: Systematic observation was used to assess implementation in two elementary schools. Participants were seven teachers and 170 students between 8 and 12 years old (87 girls and 83 boys). Results: Teachers' adherence to the model was deemed moderate, with varied application of established responsibility-based teaching strategies. Teachers had notably lower scores related to promoting life skill transfer. However, the strategies teachers used to foster responsibility were significantly correlated with their students' demonstration of responsible behaviors. Discussion/Conclusion: Results indicate TPSR may provide an effective framework for promoting responsibility across the school curriculum. Implications for research and strategies for promoting implementation fidelity are discussed.